WEB-BASED FOOD & BEVERAGE ORDERING INFORMATION SYSTEM, WEB-BASED INFORMATION SYSTEM AT TUTUG ONCOM RESTAURANT WITH USING THE FCFS METHOD - Muhamad Yandi; Ai Rosita (JURNAL DARMA AGUNG, 2023)
In the current era, technological developments are developing rapidly in various regions. The technology that is currently popular, namely mobile technology , uses various sophistication in the world of entertainment, education to the business world. Advances in technology have many advantages and benefits that can streamline when doing work. as a model for ordering culinary and drinks at a restaurant. This food and beverage ordering software is used to make it easier for customers to place food and beverage orders without having to wait in long queues, so a food and beverage ordering software was built using the FCFS (First Come First Served ) method on webservice- based QR Code technology . As long as there will be several tests, it can be concluded in this study that the average waiting value for customers is from three customers, namely 12.33 minutes , and from five customers, namely 42.4 minutes. create a webservice using the HTTP protocol with the flow of creating a database , service , web/ backend , using a UML waterfall .